Gaya Bahasa dalam Lirik Lagu Kepada Noor-Panji Sakti - Amrullah, Asyraf; Shadiqin, Muhammad Irsyad Ash (STKIP PGRI Ponorogo Press, 2024)
This research aims to examine the authentic meaning of the lyrics of the song